The Effect of Habits of Mind on Mathematical Problem-Solving Ability of Junior High School Students - Neng Yustinah; Euis Eti Rohaeti; Anik Yuliani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Mathematical problem-solving ability is one of the cognitive aspects that must be mastered by students in order to be able to solve problems that are often encountered in everyday life. In addition to the cognitive aspect there are affective abilities, one of which is the Habits of Mind. This study aims to analyze and examine in depth the problem-solving abilities that are influenced by the habits of mind in junior high school students. The method in this study uses a correlational method with a quantitative approach. The populational in this study were junior high school students in Bekasi Regency and a sampel of 38 people who were determined by purposive sampling technique at one junior high school in Bekasi Regency. The instrument used is in the form of a problem-solving ability test with 3 questions and a Habits of Mind scale with 25 statements. The resulth of this study concluded that there were 50% high habits of mind with moderate problem-solving abilities, 15.79% high habits of mind and high problem-solving abilities, 13.16% moderate habits of mind and moderate problem-solving abilities, 21.05% moderate habits of mind and low problem-solving abilities. In addition, there is a positive influence between the habits of mind and the mathematical problem-solving abilities of junior high school students by 20.40%. This show that the higher students’ habits of mind, the higher the problem-solving ability of students. Based on the result, it is necessary to carry out further research on habits of mind and students’ mathematical problem-solving abilities.